PENGARUH KEPEMIMPINAN ETIS DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA KARYAWAN KOPERASI BATIK DI JOGJAKARTA - Jajuk Herawati; Prayekti Prayekti (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2015)
This study aims to determine the influence of ethical leadership and organizational commitment to employee performance, as well as the influence of ethical leadership on organizational commitment. The rp was carried out as a survey. The population of this study were all employees in the city of Yogyakarta batik cooperatives. Sampling was done by purposive sampling. Number of samples was 37 people, 8 people from enlisted KBTamtama, 9 people from KB Senopati, 6 people from KB PPBI, 7 people from Coral Single Family Planning, and 7 people from KB Mataram. Data were collected using a questionnaire that has been tested for validity and reliability. Scale measurements using 5-point Likert scale. Hypothesis testing is done by using multiple regression analysis and simple regression analysis. The results showed: (1) ethical leadership had positive and significant effect on employee performance (b = 0755; p = 0.000 <0.05). The implication, the better implementation or application of ethical leadership from the head, then the employee's performance is likely to increase; (2) organizational commitment had positive and significant impact on employee performance (b = 0.490; p = 0.002 <0.05). The implication, the stronger the organizational commitment of employees, then the employee's performance is likely to increase; and (3) ethical leadership hadpositive and significant effect on organizational commitment (b = 0629; p = 0.000 <0.05). The implication, the better implementation or application of ethical leadership of the leadership, the organizational commitment of employees tend to increase.Â Keywords : ethical leadership, organizational commitment, employee performance, purposive sampling.